2016
DOI: 10.1111/jsbm.12275
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Entrepreneurial Burnout in a Moderated Mediated Model of Job Fit

Abstract: We introduce, and empirically test, a model of entrepreneurial burnout that highlights the relationships among job fit, entrepreneurial passion, destiny beliefs, and burnout. Using a sample of 326 individuals involved in entrepreneurial jobs, we tested the link between job fit and two forms of passion—harmonious and obsessive—and the moderating role of entrepreneurs' destiny beliefs about work (i.e., the belief that a successful career is “meant to be”). Findings illustrated that their job fit perceptions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 80 publications
(120 reference statements)
4
58
0
2
Order By: Relevance
“…In line with this definition, researchers have adapted Vallerand et al’s (2003) scales of harmonious and obsessive passion to fit the entrepreneurial setting, asking respondents to rate both dimensions of passion in relation to work activities associated with their entrepreneurial business. Although some researchers have used the seven‐item scales from Vallerand et al (2003) to measure harmonious and/or obsessive passion (Gielnik, Uy, Funken, & Bischoff, 2017; Stroe et al, 2018a, 2018b), others have used abbreviated scales comprising six items (Ho & Pollack, 2014; Stenholm & Nielsen, 2019), five items (Dalborg, von Friedrichs, & Wincent, 2015; Dalborg & Wincent, 2015; de Mol, Ho, & Pollack, 2018; Murnieks, Mosakowski, & Cardon, 2014; Obschonka et al, 2019; Thorgren & Wincent, 2015) and four items (Fisher, Merlot, & Johnson, 2018). Full or adapted versions of the scales have been used in 14 quantitative studies at the individual level.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with this definition, researchers have adapted Vallerand et al’s (2003) scales of harmonious and obsessive passion to fit the entrepreneurial setting, asking respondents to rate both dimensions of passion in relation to work activities associated with their entrepreneurial business. Although some researchers have used the seven‐item scales from Vallerand et al (2003) to measure harmonious and/or obsessive passion (Gielnik, Uy, Funken, & Bischoff, 2017; Stroe et al, 2018a, 2018b), others have used abbreviated scales comprising six items (Ho & Pollack, 2014; Stenholm & Nielsen, 2019), five items (Dalborg, von Friedrichs, & Wincent, 2015; Dalborg & Wincent, 2015; de Mol, Ho, & Pollack, 2018; Murnieks, Mosakowski, & Cardon, 2014; Obschonka et al, 2019; Thorgren & Wincent, 2015) and four items (Fisher, Merlot, & Johnson, 2018). Full or adapted versions of the scales have been used in 14 quantitative studies at the individual level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Murnieks et al (2018) found that this relationship was significantly stronger for male entrepreneurs. Recent work has found a strong link between an entrepreneur’s person‐job fit and their harmonious passion (de Mol et al, 2018). However, they also found that the link between an entrepreneur’s person‐job fit was only related to their obsessive passion when destiny beliefs were high but not when they were low.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple roles place a higher demand on entrepreneurs and lessen their capabilities to perform [48][49][50][51]. Generally, entrepreneurs emotionally connect to their ventures, and hence, any results that are contrary to their expectations creates entrepreneurial stress [52,53]. Entrepreneurs show a desire for high achievement, and when their ambitious goals are unfulfilled, it can create perceived entrepreneurial stress [54].…”
Section: Personal Stressor: Capability Gapmentioning
confidence: 99%